Influenza A H3N2-Associated Meningoencephalitis in an Older Adult With Viral RNA in Cerebrospinal Fluid: Case Report - Dou, Yu-chao; Li, Yu-qing (Frontiers in Neurology, 2022)
Influenza-associated encephalopathy (IAE) is most frequently observed in young children, but less reported in adults. Diagnosis of IAE is difficult, as clinical presentations vary significantly and the influenza virus is rarely detected in cerebrospinal fluid (CSF). Herein, we described the case of an older adult presenting with acute meningoencephalitis due to an influenza A (H3N2) infection and the influenza A (H3N2) RNA is detected in cerebrospinal fluid. To the best of our knowledge, this is infrequently reported in the literature. We emphasize that, in adults presenting with acute viral encephalitis, clinicians should consider an influenza infection as part of the differential diagnosis and that metagenomic next-generation sequencing of CSF for IAE may help establish an accurate diagnosis. It must be emphasized that the administration of steroids in a timely manner following the onset of symptoms may yield a better outcome in patients.